2016
DOI: 10.1093/gji/ggw218
|View full text |Cite
|
Sign up to set email alerts
|

Aftershock seismicity and tectonic setting of the 2015 September 16 Mw 8.3 Illapel earthquake, Central Chile

Abstract: Powerful subduction zone earthquakes rupture thousands of square kilometres along continental margins but at certain locations earthquake rupture terminates. To date, detailed knowledge of the parameters that govern seismic rupture and aftershocks is still incomplete. On 2015 September 16, the Mw 8.3 Illapel earthquake ruptured a 200 km long stretch of the Central Chilean subduction zone, triggering a tsunami and causing significant damage. Here, we analyse the temporal and spatial pattern of the coseismic rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
(36 reference statements)
5
8
0
Order By: Relevance
“…A similar along-dip seismicity gap, albeit more pronounced, was observed in the aftershock series of the 2010 M8.8 Maule earthquake as well as before and after the 2015 M8.3 Illapel earthquake and has been suggested to be a general pattern of the megathrust seismicity in central Chile (Lange et al, 2016). The aseismic area separating the shallower and deeper clusters has been shown to approximately correlate with the continental Moho in south-central Chile (Lange et al, , 2016. Our relocated seismicity confirms the occurrence of an aseismic zone, suggesting that this particular depth segmentation of the megathrust seismicity may be generic along most of the Chilean subduction zone.…”
Section: Relation Between Coseismic Slip Afterslip and Aftershock Ssupporting
confidence: 63%
“…A similar along-dip seismicity gap, albeit more pronounced, was observed in the aftershock series of the 2010 M8.8 Maule earthquake as well as before and after the 2015 M8.3 Illapel earthquake and has been suggested to be a general pattern of the megathrust seismicity in central Chile (Lange et al, 2016). The aseismic area separating the shallower and deeper clusters has been shown to approximately correlate with the continental Moho in south-central Chile (Lange et al, , 2016. Our relocated seismicity confirms the occurrence of an aseismic zone, suggesting that this particular depth segmentation of the megathrust seismicity may be generic along most of the Chilean subduction zone.…”
Section: Relation Between Coseismic Slip Afterslip and Aftershock Ssupporting
confidence: 63%
“…The 2015 M w 8.3 Illapel earthquake was the most recent event in the north of the study area, and occurred where similar-sized events in 1880 and 1943 had been registered (Figure 2a). The northern and southern termination of their rupture areas coincide with where the Challenger Fracture Zone (CFZ) and Juan Fernández Ridge (JFR) are subducted (Tilmann et al, 2016;Lange et al, 2016), consistent with the suggestion that such seafloor features can be efficient rupture barriers along the Chilean margin (e.g. Contreras-Reyes and Carrizo, 2011;Sparkes et al, 2010).…”
Section: Study Areasupporting
confidence: 75%
“…Along-strike changes in the behaviour of the plate interface are thought to be primarily controlled by plate interface roughness, which is often a consequence of the subduction of seafloor relief (Contreras-Reyes and Carrizo, 2011; Bassett and Watts, 2015;van Rijsingen et al, 2019). Clearly identifiable seafloor features, the Challenger Fracture Zone to the north and the Juan Fernández Ridge to the south (marked in Figure 2b; shown in more detail in Figure S2), likely acted as delimiters of the 2015 Illapel earthquake (Figure 2b Tilmann Lange et al, 2016;Poli et al, 2017). The microseismicity extending to shallow depths we observe both north and south of the Illapel rupture (Figure 2b,c) could thus be linked to the ongoing subduction of these features.…”
Section: The Nature Of the Along-strike Separatorsmentioning
confidence: 99%
“…In contrast, it has been suggested that subducting seamounts can nucleate great subduction earthquakes [ Scholz and Small , ; Duan , ]. Lange et al [] have mapped the subducting seamounts of JFR in the southern boundary of the Illapel earthquake. The locking models of Tilmann et al [] and Métois et al [] show that the subducting JFR was a region of relative low locking as compared with the surrounding regions.…”
Section: Discussionmentioning
confidence: 99%